Earlier is Better. New Options for Acute Heart Failure: When, Who, How Much? - Nechita Alexandru Cristian (Sciendo, 2022)
Heart failure (HF) is a major public health problem characterised by a high rate of hospitalisation and death. The risk is maximal for patients admitted with acute heart failure (AHF). New therapies with solid proof of mortality reduction in both groups of patients with reduced and preserved ejection fraction (EF) are now available (valsartan/sacubitril and SGLT2 inhibitors).